Highly transparent Mg0.27Al2.58O3.73N0.27 ceramic fabricated by aqueous gelcasting, pressureless sintering, and post‐HIP. Issue 11 (23rd May 2019) - Zong, Xiao; Wang, Hao; Gu, Honggang; Ren, Lu; Guo, Shengqiang; Tu, Bingtian; Wang, Weimin; Liu, Shiyuan; Fu, Zhengyi
Abstract: Magnesium aluminum oxynitride (Mg0.27 Al2.58 O3.73 N0.27, termed as MgAlON) ceramics with high transparency and complicated shape was prepared by aqueous gelcasting, pressureless sintering, and followed by hot isostatic pressing. No obvious hydration was found by the characterizations of X‐ray diffraction, pH value, Fourier transform infrared and thermal analysis for the interaction between MgAlON spinel powders and water, leading to the stable MgAlON slurry with high solid loading (52 vol%) and low viscosity. This result may be due to different composition of MgAlON from that of MgAl2 O4 and AlON. Besides, transparent MgAlON ceramic (1.95 mm in thickness) with a high in‐line transmittance ~86.3% at 3.7 μm was fabricated. The refractive index ~1.7499 at 589.3 nm and absorption coefficient ~1.2 cm −1 at 5 μm of MgAlON are between those of AlON and MgAl2 O4 transparent ceramics, and Abbé number ~73.66 of MgAlON is the highest.